Apulian infectious diseases network: survey on the prevalence of delta infection among chronic HBV carriers in Apulia - Fasano, Massimo; Milella, Michele; Carbonara, Sergio; Tundo, Paolo; Minniti, Salvatore; Buccoliero, Giovanni; Maci, Anna Maria; Lo Caputo, Sergio; Santantonio, Teresa Antonia (Frontiers in Public Health, 2023)
Background: The current prevalence and clinical burden of Hepatitis Delta Virus (HDV) infection in Apulia are unknown. This study aimed to define the current epidemiological scenario of delta infection and to detect difficulties in the diagnosis and clinical management of HDV patients in Apulia. Methods: From May to September 2022, a fact-finding survey was conducted at eight Infectious Diseases Units of the Apulian region; each Unit was asked to compile a questionnaire on screening and diagnosis of HDV infection and demographic, virological, and clinical characteristics of HDV patients. Results: A total of 1461 HBsAg-positive subjects were followed up on an outpatient basis. Screening for HDV ranged from 30% to 90% of HBsAg+ carriers in a single Centre. Of the 952 HBsAg+ subjects (65%) tested for HDV, 80 (8.4%) were anti-HDV positive, but only 19% were tested for HDV RNA. Most of the anti-HDV-positive subjects (81%) were from Italy; risk factors for HDV acquisition included the presence of HDV infection in the family (36%), drug addiction (15%), and co-infection with HCV (6%), or HIV (3%). Liver cirrhosis was diagnosed in 51% of patients, and 71% received nucleos(t)ide analogue treatment. Conclusions: Real HDV prevalence data in Apulia are lacking and HDV screening is variable and insufficient. Moreover, the HDV RNA test is not available in most laboratories and is not provided by the national health system. These data underline the need to develop an organizational model to optimize the management of HDV patients throughout the region